Pemberdayaan Jemaat dalam Pelestarian Lingkungan Berbasis Etika Alkitabiah - Marbun, Ernida (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2025)
The global environmental crisis demands a comprehensive response from various institutions, including religious communities. This study explores the potential for empowering Christian congregations in environmental conservation efforts through a biblical ethical approach. This study analyzes the theological foundations of environmental conservation, an effective model of congregational empowerment, and the practical implementation of biblical ethics in a contemporary ecological context by using a qualitative methodology that includes a hermeneutic-theological approach and a participatory case study. The research findings indicate that the concept of stewardship in the Christian tradition provides a strong ethical foundation for active congregational involvement in environmental conservation. The developed empowerment model integrates spiritual, educational, and practical dimensions through a participatory approach involving all congregation members. Program implementation demonstrated a significant increase in ecological awareness, changes in environmentally friendly behavior, and communal engagement in conservation initiatives. This study contributes to the development of practical ecological theology, providing a framework for mobilizing religious communities to address environmental challenges. Practical implications include the development of faith-based ecological education curricula, ecotheological communication strategies, and partnership models between religious institutions and environmental organizations. Abstrak Krisis lingkungan global menuntut respons komprehensif dari berbagai institusi, termasuk komunitas religius. Penelitian ini mengeksplorasi potensi pemberdayaan jemaat Kristen dalam upaya pelestarian lingkungan melalui pendekatan etika Alkitabiah. Menggunakan metodologi kualitatif dengan pendekatan hermeneutik-teologis dan studi kasus partisipatif, penelitian ini menganalisis landasan teologis pelestarian lingkungan, model pemberdayaan jemaat yang efektif, dan implementasi praktis etika Alkitabiah dalam konteks ekologis kontemporer. Temuan penelitian menunjukkan bahwa konsep stewardship (penatalayanan) dalam tradisi Kristen menyediakan fondasi etis yang kuat untuk keterlibatan aktif jemaat dalam pelestarian lingkungan. Model pemberdayaan yang dikembangkan mengintegrasikan dimensi spiritual, edukatif, dan praktis melalui pendekatan partisipatif yang melibatkan seluruh anggota jemaat. Implementasi program menunjukkan peningkatan signifikan dalam kesadaran ekologis, perubahan perilaku ramah lingkungan, dan keterlibatan komunal dalam inisiatif pelestarian. Penelitian ini berkontribusi pada pengembangan teologi ekologi praktis dan memberikan bingkai kerja untuk mobilisasi komunitas religius dalam menghadapi tantangan lingkungan. Implikasi praktis mencakup pengembangan kurikulum pendidikan lingkungan berbasis iman, strategi komunikasi ekoteologi, dan model kemitraan antara institusi religious dan organisasi lingkungan.